Normative Conditions- Logistics Factor of Development of Ports for Nautical Tourism - Kovačić, Mirjana; Luković, Tihomir; Dundović, Čedomir (Promet - Traffic&Transportation, 2008)
This paper presents systematically and concisely legal regulationsimportant for nautical tourism and the operation ofnautical ports. The authors have examined the cu'ent legalsystem and considered and determined its implementation androle in the development of nautical tourism. The developmentof nautical tourism requires complex legal regulation becausepublic and private interests, international conventions and nationalregulations and numerous elements of navigation safetyare interlinked at different levels. The developed Medite'aneancountries like Spain, France and Italy have very old regulationsand efficient systems for enforcing and upgrading them. Thesystem of enforcing the laws, testing them and decreasing therisks and difficulties which may arise from inadequate formulationsis often more important than the law itself The less developedcountries, like Croatia and Greece, have not acceptedthe problem, and therefore create a certain degree of legal insecurityand inefficiency of the enforced laws. The paper has definedand analysed the existing problems and indicated the possiblesolutions. The development of a logistics system of normativeconditions relating to nautical tourism and nautical tourismports has been defined and a logistics model of strategic decision-making presented.